HUBUNGAN PERAWATAN DIRI DENGAN KEJADIAN CACAT KUSTA DI WILAYAH KERJA PUSKESMAS PULAU KIJANG INDRAGIRI HILIR RIAU - Cendrawirda, Sri Wardani, (Menara Ilmu, 2018)
Leprosy is an infectious disease that does not cause death directly and can be cured with thetreatment of Multi Drug Treatment (MDT), but the disease will cause lifelong disability for leprosypatients who are not treated properly and will become a public health problem. If the leprosydisease that has experienced disability then the effort that needs to be done is self-care for thedefects suffered do not become more severe and acceptable again in the community. PuskesmasKijang Island with the highest number of leprosy cases in Indragiri Hilir Regency and many peoplewith disabilities. For that we need to do research. This study aims to determine the relationship ofself care with the incidence of leprosy defects in Puskesmas Kijang Island Indragiri Hilir Regency.The research method is done by case control study. Population in this research is all leprosypatients recorded in leprosy registers of Puskesmas counted 47 people. Sampling was done in totalsampling. Data analysis was done by univariate analysis (tendency central) and bivariate analysis(chi square test) and collected data was processed by computerized method. The results of thisstudy found that 47 people with leprosy who did self-care as many as 28 people (59.6%) and whodid not care self as much as 19 people (40.4%). Of the 47 people who suffered from disability, thedisease continued as many as 18 people (38.3%) and who did not experience disability by 29people (61.7%). The result of bivariate test showed that there was a correlation between self-careand leprosy incidence (pvalue = 0.01) and the value of OR 6.3 means that leprosy patients who didnot take care of themselves were at risk for disability 6.3 times higher than those who did not care.It is advisable to prevent leprosy from getting worse alias the occurrence of disability to leprosypatients to understand early disease and take care of themselves regularly.